1995
DOI: 10.1016/0014-5793(95)00067-j
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‐mediated production of nitric oxide in isolated rat hepatocytes is dependent on cytochrome P‐450III activity

Abstract: To investigate the role of the cytochrome P-450 system in NO synthesis, cytochrome P-450IIIA, IIE and IA activities were specifically inhibited by cimetidine (IIIA), clotrimazole (IIIA), benzoflavone (IA) and disulfiram (IIE) in a model of cultured rat hepatocytes. Cytokine-induced NO synthesis was significantly decreased in the presence of cimetidine and clotrimazole. Kinetic analysis revealed a non-competitive mode of inhibition (K i = 21 mM, cimetidine; K i = 13/xM, clotrimazole). Reverse transcriptase-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Cell supernatants prepared from representative matched control and clotrimazole-treated cultures (500 ml each) contained 28 and 23 mg of soluble protein, respectively, indicating that clotrimazole caused little or no cell lysis under these conditions. Supernatant prepared from the clotrimazoletreated culture displayed a NO synthesis specific activity that was 6-fold lower than the control supernatant (0.38 versus 2.3 nmol of nitrite/min/mg of protein, respectively), but contained a similar amount of iNOS protein as the control as judged by Western analysis (data not shown), consistent with corresponding observations in activated hepatocytes (62). Thus, the clotrimazole-treated culture contained iNOS in a predominantly inactive form.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Cell supernatants prepared from representative matched control and clotrimazole-treated cultures (500 ml each) contained 28 and 23 mg of soluble protein, respectively, indicating that clotrimazole caused little or no cell lysis under these conditions. Supernatant prepared from the clotrimazoletreated culture displayed a NO synthesis specific activity that was 6-fold lower than the control supernatant (0.38 versus 2.3 nmol of nitrite/min/mg of protein, respectively), but contained a similar amount of iNOS protein as the control as judged by Western analysis (data not shown), consistent with corresponding observations in activated hepatocytes (62). Thus, the clotrimazole-treated culture contained iNOS in a predominantly inactive form.…”
Section: Resultssupporting
confidence: 83%
“…Our data argue for a heme-based mode of action for clotrimazole in the cells. For example, the clotrimazole-treated cells grew normally and expressed a normal amount of protein, confirming it is not toxic at the concentration used (62,71). Immunochemical and catalytic data indicated that iNOS monomers from clotrimazole-treated cells still contained a normal amount of bound CaM.…”
Section: Fig 3 Time Course Of Dimerization Promoted By Imidazolementioning
confidence: 78%
“…(1) Anti-fungal imidazoles inhibit the translation of NO synthase mRNA into protein; (2) anti-fungal imidazoles inhibit the synthesis or binding of a cofactor essential for activity of the expressed enzyme; or (3) antifungal imidazoles inhibit post-translational modification(s) necessary for the activity of NO synthase. Subsequently it has been shown that clotrimazole inhibits the induction of NO synthesis in rat hepatocytes without affecting mRNA or levels of the enzyme expressed (Kuo & Abe, 1995), indicating that translation of mRNA is not affected by these agents. In the present study we have shown that anti-fungal imidazoles are likely to act via inhibition of the activity or binding of calmodulin, which is required for activity of iNOS.…”
Section: Discussionmentioning
confidence: 99%
“…iNOS is normally not expressed in the brain and the spinal cord postnatally. However, when it is induced under certain pathological conditions such as cerebral ischemia or encephalomyelitis it synthesizes NO in nanomolar concentrations, 100 -1000 times those produced by nNOS [18], suggesting that iNOS plays an important role in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%